2015
DOI: 10.1105/tpc.15.00101
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of INDOLE-3-ACETIC ACID INDUCIBLE28 mRNA by MicroRNA847 Upregulates Auxin Signaling to Modulate Cell Proliferation and Lateral Organ Growth in Arabidopsis

Abstract: MicroRNAs function in a range of developmental processes. Here, we demonstrate that miR847 targets the mRNA of the auxin/indole acetic acid (Aux/IAA) repressor-encoding gene IAA28 for cleavage. The rapidly increased accumulation of miR847 in Arabidopsis thaliana coincided with reduced IAA28 mRNA levels upon auxin treatment. This induction of miR847 by auxin was abolished in auxin receptor tir1-1 and auxin-resistant axr1-3 mutants. Further analysis demonstrates that miR847 functions as a positive regulator of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 81 publications
(133 reference statements)
1
40
0
Order By: Relevance
“…A similar situation was observed previously for novel miRNAs isolated in this and other plant species (Mica et al, 2010;Li et al, 2011;Ren et al, 2012;Ge et al, 2013). Moreover, since miRNAs belonging to lowabundance categories have emerging big roles in plant developmental processes (Wang and Guo, 2015), we hypothesize that the analyzed novel miRNAs that are less abundant than conserved miRNAs could function to modulate the cross talk between plant development and the abiotic stress response. For instance, the novel candidate miRNA n_22 was predicted to target an MLO calmodulin-binding protein (MLO16)-encoding transcript belonging to a plant gene family involved in pathogen defense and abiotic stress response processes (Piffanelli et al, 2002).…”
Section: Conserved and Novel Grapevine Mirnas Respond To Ds In The Twmentioning
confidence: 50%
“…A similar situation was observed previously for novel miRNAs isolated in this and other plant species (Mica et al, 2010;Li et al, 2011;Ren et al, 2012;Ge et al, 2013). Moreover, since miRNAs belonging to lowabundance categories have emerging big roles in plant developmental processes (Wang and Guo, 2015), we hypothesize that the analyzed novel miRNAs that are less abundant than conserved miRNAs could function to modulate the cross talk between plant development and the abiotic stress response. For instance, the novel candidate miRNA n_22 was predicted to target an MLO calmodulin-binding protein (MLO16)-encoding transcript belonging to a plant gene family involved in pathogen defense and abiotic stress response processes (Piffanelli et al, 2002).…”
Section: Conserved and Novel Grapevine Mirnas Respond To Ds In The Twmentioning
confidence: 50%
“…A large number of candidate genes that are potentially regulated by auxins, including the ARF and IAA gene family in Arabidopsis , are targets of miRNAs (Szemenyei et al 2008; Chandler 2016). Previously, we demonstrated that auxin-dependent induction of miR847 is involved in regulating meristematic competence by targeting the mRNA of IAA28 to up-regulate auxin signalling (Wang and Guo 2015). Furthermore, many ARF genes are directly regulated by at least one miRNA in response to biotic or abiotic stress, such as ARF6 and ARF8 are targeted by miR167 while ARF10, ARF16 and ARF17 are targeted by miR160 (Chandler 2016; Li et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another detailed study reported by Gutierrez et al (2012), demonstrated the coordinated roles of miR160 and miR167 targeting auxin responsive genes indispensable for root architecture remodeling. Similarly, overexpression of miR847 exhibited more lateral roots thereby modulating indole acetic acid (IAA) related genes (Wang and Guo, 2015). Plants respond according to the availability status of macroand micro-nutrients and in turn adapt certain strategies at the molecular level in order to efficiently use available resources.…”
Section: Root Architecture Modifications To Optimize Nutrient Acquisimentioning
confidence: 99%